Study roadmap for high-throughput development of easy to use and affordable biomarkers as diagnostics for tropical diseases: a focus on malaria and schistosomiasis - Kokouvi Kassegne; Ting Zhang; Shen-Bo Chen; Bin Xu; Zhi-Sheng Dang; Wang-Ping Deng; Eniola Michael Abe; Hai-Mo Shen; Wei Hu; Takele Geressu Guyo; Solomon Nwaka; Jun-Hu Chen; et al. (BMC, 2017)
Abstract Background Interventions are currently being used against 'infectious diseases of poverty', which remain highly debilitating and deadly in most endemic countries, especially malaria, schistosomiasis, echinococcosis and African sleeping sickness. However, major limitations of current 'traditional' methods for diagnosis are neither simple nor convenient for population surveillance, and showed low sensitivity and specificity. Access to novel technologies for the development of adequate and reliable tools are expressly needed. A collaborative project between African Network for Drugs and Diagnostics Innovation and partner institutions in Africa and China aims to screen suitable serological biomarkers for diagnostic pipelines against these 'diseases of the poor'. Methods Parasite-specific exposed versus unexposed individuals were screened and sera or urine/stools were collected through case-control studies in China and African countries. Target genes/open reading frames were selected, then will be cloned and cell-free expressed, quantified and immuno-detected. Target antigens/epitopes will be probed and screened with sera from exposed or unexposed individuals using a high-throughput antigen screening platform as the study progresses. The specificity and sensitivity of highly immunoreactive biomarkers will be evaluated as well, using enzyme-linked immunosorbent assays or dipsticks. Discussion This roadmap explicitly unfolds the integrated operating procedures with focus on malaria and schistosomiasis, for the identification of suitable biomarkers that will aid the prioritization of diagnostics for population use. However, there is need to further validate any new diagnostic through comparison with standard methods in field deployable tests for each region. Our expectations for the future are to seek regulatory approval and promote the use of diagnostics in endemic areas.